Buddhist nonduality, Paschal paradox: a Christian commentary on The teaching of Vimalakīrti (Vimalakīrtinirdeśa) - O'Leary, Joseph Stephen (Christian commentaries on non-Christian sacred texts, 2018)
"The Teaching of Vimalakirti', treasured in China and Japan and best known in the West in Canon Étienne Lamotte's classic translation from the Tibetan and Chinese, has now surfaced in its original language, Sanskrit, after two thousand years. Centered on a lay bodhisattva, a master of paradox, who has no equal in debate except the Buddha and Manjusri, the embodiment of wisdom, 'Vimalakirti' is the most humorous and engaging of the major Buddhist scriptures, comparable to the Book of Job in its dramatic format. In the first commentary on the recovered text, an Irish theologian reads 'Vimalakirti' and the Gospels in light of each other, and finds resonances between the Buddhist wisdom of nonduality and the Christian dynamic of incarnation and paschal transformation."